Proposal for introduction of ocean thermal energy conversion (OTEC) to the energy sector of Bangladesh - Shakil, Shifur Rahman; Hoque, Md. Anamul (© 2013 IEEE Computer Society, 2017)
This conference paper was presented in the 2nd International Conference on Advances in Electrical Engineering, ICAEE 2013; Dhaka; Bangladesh; 19 December 2013 through 21 December 2013 [© 2013 IEEE] The conference paper's definite version is available at: http://dx.doi.org/10.1109/ICAEE.2013.6750366